Integrująca rola religii w wychowaniu ekologicznym - Piotr Krajewski (Nicolaus Copernicus University in Toruń, 2011)
Curricula taught across all tiers of schooling are devised to promote proecological attitudes. Religion instructors, alongside educators, should thus be involved in the schooling processes. Their teaching practice ought to remain in line with existing legislation and the social doctrine of the Church. Ecological issues were in the focus of special attention of the Pope Paul VI and John Paul II. Steps to bring ecology into religion teaching are also taken in the form of an interest which religion instructors express about the need to combine eco-awareness imparted as part of religion classes with holistic approach towards the moulding of human personality. Every man tends to perceive nature as a value and simultaneously as the common good of humanity. Respect for the environment, including all its living and non-living components, is regarded as the sine qua non of our life. The Catholic Church's stance on environmental issues ought to be incorporated into pastoral preaching and religion classes to provide food for thought. Eco-awareness is a factor shaping relationships between people and forging a positive attitude towards other forms of life. Joint collaboration of the Church and school may inculcate in young people respect for nature and encourage them to adopt a proper attitude towards ecological matters, which can be attained through assimilation of the latter into religious education.